2017
DOI: 10.21101/cejph.a4495
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Health Risk Assessment of PM<sub>10</sub> Aerosol in Brno, Czech Republic

Abstract: SUMMARYObjective: The main effort of this work was to evaluate the situation of the atmosphere in selected regions of Brno during the years 2009-2013 and to estimate health risks which might come up due to the increased concentrations of airborne particulate matter.Methods: PM 10 samples were collected in four areas varying in degree of automobile traffic using automatic and gravimetric sampling methods. PM 10 concentrations were assessed using Spearman's rank correlation coefficient. Health risks were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
(23 reference statements)
0
11
0
1
Order By: Relevance
“…Numerous studies reported the level of PM in cities all over the world [1,[30][31][32][33]. Human health risk assessment studies regarding PM 10 and toxic elements in PM 10 were also carried out in several cities [34][35][36][37][38][39]. These studies revealed that although PM concentrations do not exceed air quality standards, the health impacts associated to air pollution exposure are still important [40].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported the level of PM in cities all over the world [1,[30][31][32][33]. Human health risk assessment studies regarding PM 10 and toxic elements in PM 10 were also carried out in several cities [34][35][36][37][38][39]. These studies revealed that although PM concentrations do not exceed air quality standards, the health impacts associated to air pollution exposure are still important [40].…”
Section: Introductionmentioning
confidence: 99%
“…The 36 published papers came from various countries; six were from India [ 4 , 24 , 25 , 26 , 27 , 28 ], three from the USA [ 29 , 30 , 31 ], 14 from China [ 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and one each from Korea [ 45 ], Czech Republic [ 46 ], Canada [ 47 ], France [ 48 ], Yugoslavia [ 49 ], Japan [ 18 ] and Sweden [ 50 ]. There were four global studies [ 1 , 51 , 52 , 53 ] and two studies from the Asian region [ 54 , 55 ] ( Table 1 and Table 2 , Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Last but not least, scrubbing systems have widely been recognized in separation of particulate matter [8][9][10][11][12], the release of which is due mostly to various combustion processes [13][14][15] and, for example, comminution technologies [16,17]. This is very important due to associated health and environmental concerns [18,19]. Comparing the ability to remove particulate and gaseous pollutants, gas scrubbers have lower efficiency in one cleaning cycle but are able to treat a significantly higher amount of polluted air compared to, for example, air filtration or membrane contactors [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%